Commemorating Humayun: Emperor Akbar, the Akbarnama and the Tomb of Humayun (c.1570–1605). (2nd January 2018) - Geevers, Liesbeth
Abstract : This essay discusses the commemoration of the Mughal emperor Humayun (r. 1530–40, 1555–56) by his son Akbar (r. 1556–1605), focusing both on Akbar's practice of visiting the tomb and the way in which these tomb-visits were dealt with by contemporaneous chroniclers. The article shows how Akbar's chief ideologist, Abu'l Fazl, misrepresented Akbar's history of visiting his father's tomb, predating these visits by decades and exaggerating their extent. This manipulation of history formed part of Akbar's broader effort to present himself as a sacred ruler who was unchallenged by his own dynasty.